Language Learning Strategies in Relation to Learners’ Motivation - Nuning Ayu Wandira; Endah Nur Tjendani; Aminullah Aminullah (Linguapedia, 2017)
Writing is one of four language skills that should be mastered by students in learning English. Every student has different learning strategy in writing which help them to make their own learning effective. Motivation is one of the factors that influenced students’ learning strategies both intrinsic and extrinsic motivation had contributed in students’ learning strategies in writing skill. It can be seen from their writing achievement. This research aims to investigate the students’ learning strategies and students’ motivation towards writing achievement. The design was quantitative research. The research was applied to 35 Eleventh Science 3 grade in SMAN 1 Pakusari Jember. The data obtained from observation, interview, and documentation. The research found that students’ high learning strategies in writing and high intrinsic motivation influenced in their writing achievement.